PERTANGGUNG JAWABAN HUKUM TERHADAP PELAKU PENGGELAPAN DALAM JABATAN - Sri Intan Meilan Igirisa; Mohamad Ikbal Kadir; Haspia Saprudin (Akademika : Jurnal Ilmiah Media Publikasi Ilmu Pengetahuan dan Teknologi, 2026)
This study aims to analyze the legal responsibility of perpetrators of embezzlement in office based on Indonesian criminal law. The research employs a normative juridical method with statutory and case approaches, utilizing secondary data such as legislation, court decisions, and relevant scientific literature. The results indicate that embezzlement in office is a specific criminal offense involving abuse of trust and authority attached to a position. Criminal liability is determined based on the fulfillment of both objective and subjective elements of the offense, including intent and the resulting losses. Firm law enforcement, along with preventive measures such as strengthening supervision and integrity, is essential to effectively address this type of crime